Characteristics and Properties of Myristic Acid‐Stearic Acid Based Ternary Composite Phase Change Materials for Thermal Energy Storage. Issue 37 (5th October 2022) - Pan, Yucheng; Fei, Hua; He, Qian; Wang, Linya; Liang, Ximei; Zhou, Jiahong
Abstract: In this work, melt blending method was used to prepare two composite phase change materials of myristic acid‐stearic acid (MS) and myristic acid‐stearic acid‐lauric acid (MSL). The optimum mass ratios of MS and MSL were 77 : 23 and 28 : 9 : 63 by step cooling curve assay, respectively. The phase transition temperature of MS and MSL were 47.13 °C and 28.81 °C by differential scanning calorimetry (DSC), and the latent heat of phase transition of MS and MSL were also measured to be 153.3 J/g and 143.3 J/g, respectively. On the other hand, the phase transition temperature of MSL had little change after 300 cycles, indicating that it had good stability. In addition, the structure characteristics of MSL was found to be the same as that of pure material by FTIR, which indicates that materials are interacted by molecular force. Therefore, MSL can be used in construction and has a good application prospect. Abstract : A myristic acid‐stearic acid‐lauric acid composite phase change material (MA‐SA‐LA) was prepared by melt blending method. Determine the mixing ratio of myristic acid, stearic acid and lauric acid with combining theory and experiment and obtain composite phase change materials with good thermal properties and stable chemical properties.